2020
DOI: 10.1155/2020/9127465
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Reconstructed Frontal Face Images Using FFT-PCA/SVD Algorithm

Abstract: Face recognition has gained prominence among the various biometric-based methods (such as fingerprint and iris) due to its noninvasive characteristics. Modern face recognition modules/algorithms have been successful in many application areas (access control, entertainment/leisure, security system based on biometric data, and user-friendly human-machine interfaces). In spite of these achievements, the performance of current face recognition algorithms/modules is still inhibited by varying environmental constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…The findings of the study are consistent with those of Asiedu et al [6] and Singh and Nandi [5]. The DWT-PCA/SVD algorithm is recommended as a suitable algorithm for face image recognition under partial occlusion (half face images).…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings of the study are consistent with those of Asiedu et al [6] and Singh and Nandi [5]. The DWT-PCA/SVD algorithm is recommended as a suitable algorithm for face image recognition under partial occlusion (half face images).…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
“…The main numerical performance metrics adopted for assessment of the study algorithm (DWT-PCA/SVD) were the average recognition rate and computational time (runtime of the algorithm). According to Asiedu et al [6], the average recognition rate, R avg , of an algorithm is given as…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdul-Jabbar [3] showed that preprocessing steps such as image adjustment, histogram equalization, and change in file format when applied to enhance the contrast and the quality of face images in different face recognition algorithms improve the accuracy of recognition up to 30% as compared to using the original database of face images. In the case where half of the face is degraded due to occlusions, several researchers [4,5] have leveraged the bilateral symmetry of face images to reconstruct the full-face images and have used different denoising techniques to enhance image quality. Asiedu et al [4] reconstructed frontal face images from left and right-half images using principal component analysis and singular value decomposition (FFT-PCA/SVD) and employed fast Fourier transforms in the preprocessing stage.…”
Section: Introductionmentioning
confidence: 99%